Patient safety culture and obstacles to adverse event reporting in nursing homes. (26th August 2020) - He, Haiyan; Yu, Pingping; Li, Li; Xiao, Xueling; Long, Yanfang; Wang, Liqian; Zeng, Jiaqi; Li, Yinglan
Abstract: Aims: To investigate patient safety culture and its relationship with obstacles to adverse event reporting in Chinese nursing homes. Background: Reporting obstacles are related to high incidences and unreported rates of adverse events. Patient safety culture is also associated with adverse events. However, the relationship between reporting obstacles and patient safety culture in nursing homes is unclear. Methods: A cross‐sectional survey was conducted with a random sampling method among 549 staff members in six nursing homes using instruments of the Nursing Home Survey on Patient Safety Culture and the Adverse Event Reporting Obstacle Scale. The Pearson correlation coefficient, independent t tests, ANOVA tests and multivariate regression analysis were used. Results: Patient safety culture in nursing homes was associated with facility ownership ( p  < .001), facility scale ( p  < .001), reporting management ( p  < .001), whether it was an integrated care institution ( p  = .006), frequency of concern about patient safety ( p  = .001), occurrence of adverse events in departments ( p  = .001) and a punitive atmosphere ( p  = .044). Adverse event reporting obstacles were negatively correlated with patient safety culture ( p  < .05). Conclusion: An improvement in patient safety culture was associated with a reduction in reporting obstacles in nursing homes. Implications for Nursing Management: A barrier‐free adverse event reporting system should be built to reduce reporting obstacles and create a non‐punitive patient safety culture in nursing homes.